STUDY LITERATUR: UPAYA DETEKSI DINI DAN PENCEGAHAN NPD (NARCISSISTIC PERSONALITY DISORDER) DI SEKOLAH TAHUN 2020-2025 - Sri Wahyuni; Panca Dewi Purwati; Ali Formen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This paper discusses the increasing attention to the mental health of elementary school-aged children, particularly regarding the potential for the emergence of Narcissistic Personality Disorder (NPD) symptoms at an early age. The school environment plays a crucial role in shaping a child's personality and social behavior, making early detection and prevention of NPD crucial. This paper aims to review research trends on early detection and prevention strategies for NPD in schools between 2020 and 2025, encompassing psychological approaches, the roles of teachers and school counselors, and the effectiveness of implemented interventions. This research method uses a systematic literature review approach by analyzing 20 Google Scholar-indexed journal articles relevant to the topic of NPD in elementary school-aged children during that time period. The results of the study indicate that (1) research on NPD in the school environment has begun to increase post-pandemic with a focus on children's mental health and social behavior, (2) early detection strategies utilize behavioral observation, simple psychological assessments, and parental involvement, and (3) effective prevention efforts are carried out through character education, empathy building, and emotional management in the classroom. The conclusion of this study confirms that early detection and prevention of NPD in students at school is very important for building an emotionally healthy learning environment, and can be a basis for developing psychological intervention programs in schools in the future.